SPATIAL DESIGN ANALYSIS DALAM PROSES PERENCANAAN DAN PERANCANGAN INTERIOR - Cahyatika Try Widiyanti (Ide dan Dialog Desain Indonesia (Idealog), 2018)
The design of inner space or better known as interior design is the study of design in a building and used to solve human problems. One of scientific studies based on design science, this scientific field aims to beable to create a built environment (inner space) along with its supporting elements, both physical and non-physical. So that the quality of human life in it becomes better.The interior design process aims to solve complex problems related to human response to space. To be able to solve the problem in its entirety, it requires an appropriate design concept. The success of the design concept depends on the approach taken in the preparation process.Interior spatial concepts can be built by understanding several things, including: components of design understanding, analytical design schemes, design mindset mapping, design approach methods, and ending with the design concept used in interior planning & design processes. By understanding these things, a scope of interior design in solving design problems is expected to be resolved clearly and systematically, so that the process of drafting the proper interior design & planning concepts can be done more easily. The right concept will eventually be able to tie the design results into a fully integrated design